Penampilan Puyuh Betina Yang Diberikan Pakan Mengandung Tepung Limbah Tauge Fermentasi - Arnolus Umbu Pati; Ni Ketut Sri Rukmini; Ni Ketut Mardewi (Fakultas Pertanian, Universitas Warmadewa, 2020)
The provision of adequate quality and quantity rations is expected to increase the productivity of the quail. One of the efforts to improve the quality of the ration is by adding fermented bean sprouts waste flour to the ration making, because fermented bean sprouts waste flour is rich in crude protein. The purpose of this study was to determine the effect of giving fermented bean sprouts flour waste in the ration on the appearance of female quail and to determine at what level the provision of fermented bean sprouts flour waste in the ration had the greatest effect on the appearance of female quail. This study used a completely randomized design (CRD) with 4 treatments and 3 replications. Each test used 3 female quail with homogeneous body weight. The four treatments were rations without fermented bean sprouts flour waste as a control and rations containing 5%, 10%, and 15% fermented bean sprouts flour. The parameters observed were initial body weight, body weight gain, final body weight, feed consumption, and FCR (Feed Conversion Ratio). The data obtained were analyzed by analysis of variance. If between treatments shows a significant effect, then proceed with the smallest real distance test from Duncan (Steel and Torie, 1991). Based on the results of the research and discussion, it can be concluded that the addition of fermented bean sprouts flour in the grower-layer phase of female quail ration has an insignificant effect on all variables such as initial body weight, body weight gain, final body weight, ration consumption and FCR (Feed Converstion Ratio).